Hubungan Mata Pelajaran Projek Kreatif dan Kewirausahaan terhadap Minat Berwirausaha Siswa Jurusan Kuliner di SMKN 33 Jakarta - Nabila, Meilissa; Mahdiyah, Mahdiyah; Febriana, Rina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Based on data from the Indonesian Central Statistics Agency in February 2023, the number of unemployed in Indonesia reached 7.99 million with the number of unemployed in Indonesia according to vocational school education level being 2.07 million people. This is contrary to the aim of Vocational Schools to increase community participation rates in education. Vocational School graduates should be able to build their own businesses to reduce the number of unemployed in Indonesia and the number of unemployed Vocational School graduates. Based on the title of this research, a suitable research method is an associative quantitative method with survey techniques and descriptive explanation. This research has two variables which are the object of research, where Creative Project Subjects and Entrepreneurship are the independent variables (X) while the dependent variable is Student Entrepreneurial Interest (Y). This research aims to determine the relationship between PKK subjects and interest in entrepreneurship among students majoring in Culinary at SMKN 33 Jakarta. The results of the hypothesis test show that H0 is rejected and Ha is accepted, meaning that there is a relationship between the PKK subject and Culinary students' interest in entrepreneurship. The correlation coefficient (r) value shows positive and significant results, the higher the PKK subject score, the higher the interest in entrepreneurship for Culinary students. Based on the results of the research that has been conducted, it can be concluded that the creative and entrepreneurship project subjects in this research show an important role in building the interest and courage of students majoring in culinary arts at SMKN 33 Jakarta to become entrepreneurs, as well as maximizing students' entrepreneurial skills and knowledge.